Social Construction of Servicescape Liberika Coffee Cipasung, Kuningan Regency, West Java Province - Rachman, Arief Faizal; Aditya, Michael Khrisna; Gantina, Devita (Institut Pariwisata Trisakti, 2024)
This study aims to analyse social construction of servicescape Liberika Coffee as a tourist attraction in Cipasung Village, Kuningan Regency, West Java Province. The research uses a qualitative method with a constructionism paradigm, and an epistemological philosophical approach. Analysis of the study research uses an Interpretative Phenomenology Analysis (IPA) analysis tool which is able to provide a double hermeneutic understanding to the phenomenon. The findings show that the servicescape of Liberika Coffee shop on the exterior evidence is constructed in the geographical area of Cipasung Village which is equipped with physical artifacts pointing the way to the Cipasung tourist village and Cipasung Coffee Agrotourism, the Cipasung Liberika coffee mini plantation and the post-harvest process. Meanwhile, the interior evidence is constructed in the form of coffee shop ambiance, in the sort of roasting process and coffeeshop ambiance. It concludes that physical evidence of Liberika Coffee are socially constructed by social actors (farmers, roaster, processor, barista, and visitors) and technical actors (mini coffee plantation, processing into green bean, and coffee shop). Keywords: coffee shop, servicescape, social construction, tourist attraction